Internet of Vehicles - Safe and Intelligent Mobility : Second International Conference, IOV 2015, Chengdu, China, December 19-21, 2015, Proceedings - Hsu, Ching-Hsien.; Xia, Feng.; Liu, Xingang; Wang, Shangguang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Second International Conference on Internet of Vehicles, IOV 2015, held in Chengdu, China, in December 2015. The 40 full papers presented were carefully reviewed and selected from 128 submissions. They focus on the following topics: IOV architectures and applications; intelligent mobility; V2V and M2M communications; and modeling and simulations.
Keywords: Computer security; Data encryption (Computer science).; Computer software; Computer science; Software engineering; Systems and Data Security; Cryptology; Algorithm Analysis and Problem Complexity; Math Applications in Computer Science; Special Purpose and Application-Based Systems; Computers and Society